Regional and Vernacular Expressions of Shi‘i Theology: The Prophet and the Imam in Satpanth Ismaili Ginans - Visram Imran (Open Theology)
The belief that religious guidance in the worldly life is mediated through a divinely guided, human leader is central to the theology of several Ṣūfī and Shī‘ī traditions in Islam. For Shī‘ī Muslims in particular, this guide is recognised as a legitimate leader, or Imām, and along with belief in nubuwwah (prophecy), the doctrine of imāmah (legitimate leadership) forms the foundations of their theology. For specific Shī‘ī groups, like the Ismā‘īlīs, the Imām in his divine authority is believed to know the inner, esoteric teachings of the message delivered by God through the Prophet Muḥammad. This article argues that Ismā‘īlī Shī‘ī Muslims from Sindh, Gujarat, and Punjab have reinforced their belief in the doctrines of nubuwwah and imāmah over several centuries through the preservation and transmission of a genre of vernacular oral poetry known as the ginān. The word ginān literally translates to “knowledge” and these lyrical knowledge poems were composed by a hereditary line of mystic teachers who taught through them the central theological ideas of Ismā‘īlī Shī‘a Islam. Exercises in exegesis and translation are undertaken to illustrate how these two central Islamic doctrines are exemplified in the ginān literature through the personalities of the Prophet Muḥammad and Imām ʿAlī. Readers are invited to consider the crucial role that the popular and oral-literary Satpanth tradition has played in the dissemination of Islamic theological ideas across the western regions of North India, and reflect on the possibility of including such Indic languages as Gujarati within the purview of “Islamic literature.”